Interface amorphization in hexagonal boron nitride films on sapphire substrate grown by metalorganic vapor phase epitaxy. (5th April 2018) - Yang, Xu; Nitta, Shugo; Pristovsek, Markus; Liu, Yuhuai; Nagamatsu, Kentaro; Kushimoto, Maki; Honda, Yoshio; Amano, Hiroshi
Abstract: Hexagonal boron nitride (h-BN) films directly grown on c -plane sapphire substrates by pulsed-mode metalorganic vapor phase epitaxy exhibit an interlayer for growth temperatures above 1200 °C. Cross-sectional transmission electron microscopy shows that this interlayer is amorphous, while the crystalline h-BN layer above has a distinct orientational relationship with the sapphire substrate. Electron energy loss spectroscopy shows the energy-loss peaks of B and N in both the amorphous interlayer and the overlying crystalline h-BN layer, while Al and O signals are also seen in the amorphous interlayer. Thus, the interlayer forms during h-BN growth through the decomposition of the sapphire at elevated temperatures.